Creating a Balance in Bilateral Investment Treaty: A Perspective from Indonesia - Surya Oktaviandra (Andalas International Journal of Socio-Humanities, 2022)
The previous movement of Government of Indonesia (GOI) to terminate its expiring Bilateral Investment Treaties (BITs) with many countries does not mean like the end point of rigorous policy. It then leaves a question mark about the legal standing after the concession and how the government establishes a new model to create a balance in BIT. This research is conducted to, firstly, analyze the legal position of government and foreign investor in a terminated BIT. Furthermore, it will discuss how the government can take benefit through learning experience from the previous mistakes in old BITs and the latest development in international investment law. Finally, this study focuses how a balance on BIT can be achieved for both host state and foreign investor. The result of this study shows that the government did not breach any international law procedure in particular by fathoming Vienna Convention on the Law and Treaties and protection for the investor is not diminish immediately due to the existence of survival clause. Further investigation identifies that to obtain a greater benefit following the termination, GOI should develop better balanced provisions in its next BIT model. This effort can be done by taking care of principle of extraterritorial obligation, full protection and security clause, indirect expropriation, and regulatory measure clause, and most importantly how to deal with dispute settlement.